Flinovia--Flow induced noise and vibration issues and aspects-II : a focus on measurement, modeling, simulation and reproduction of the flow excitation and flow induced response /: a focus on measurement, modeling, simulation and reproduction of the flow excitation and flow induced response. II ([2019]) - Unknown
No abstract available